2018
DOI: 10.1155/2018/7242917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Silent Gastroesophageal Reflux Disease in Patients with Hypertension

Abstract: Background Gastroesophageal reflux disease (GERD) without symptoms or silent GERD can be easily missed in patients with hypertension. We aimed to investigate the prevalence of GERD, specifically the prevalence of silent GERD in hypertensive patients, and to explore its possible predictors. Methods Consecutive patients with hypertension referred to the cardiovascular clinic of Suining Central Hospital in 2016 were screened for this study. A Reflux Disease Questionnaire (RDQ) and an esophagogastroduodenoscopy (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…However, after studying some populations in central China, Li et al [ 27 ] found that 44.2% (38/86) of essential hypertensive patients had gastroesophageal reflux. Suyu et al [ 11 ] also found that the proportion of patients with hypertension with GERD was as high as 31.4% (137/436). Our findings clearly suggest that gastroesophageal reflux can lead to elevated blood pressure and essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after studying some populations in central China, Li et al [ 27 ] found that 44.2% (38/86) of essential hypertensive patients had gastroesophageal reflux. Suyu et al [ 11 ] also found that the proportion of patients with hypertension with GERD was as high as 31.4% (137/436). Our findings clearly suggest that gastroesophageal reflux can lead to elevated blood pressure and essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies showed that patients with GERD may have a higher prevalence of essential hypertension, but the results might be influenced by sample size and potentially confounding factors such as lifestyle, socioeconomic status, and underlying medical conditions, and that conclusions may not be accurate[ 9 - 11 ]. There were a few studies on this topic and little attention was paid.…”
Section: Introductionmentioning
confidence: 99%
“…There are common risk factors for GERD and hypertension, such as obesity, age, male gender, and smoking [ 38 - 40 ]. Suyu et al [ 41 ] found that hypertension is a positive predictor for GERD, especially silent GERD. In the present study, hypertensive patients were 2.6 times more liable than non-hypertensive patients to get GERD (OR = 2.6; 95% CI 1.3-5.3; p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…Своєчасне спорожнення шлунка, яке зумовлюється нормальним станом моторно-евакуаторної і секреторної функції шлунка, внутрішньошлунковим тиском, безперешкодне проходження харчових мас через воротар у дванадцятипалу кишку. Неспроможність хоча б одного з перерахованих вище компонентів веде до ГЕРХ [13,17,18].…”
unclassified
“…Водночас є публікації, в яких заперечується кореляція симптомів ГЕРХ з даними рН-моніторингу, особливо, коли мають місце позастравохідні прояви хворобинаприклад, хронічний кашель. Тест із ІПП при верифікації ГЕРХ деякі дослідники також піддають сумніву, спираючись на досить невисокі показники чутливості та специфічності методики, що становить відповідно 78,0% та 54,0% [17,23].…”
unclassified